Exploring Factors and Impacts of Contract Breaches in Medical Therapeutic Agreements - Maria Florida Kotorok (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2023)
This research addresses how social, economic, and educational factors contribute to contract breaches and explores the psychological impacts on patients and doctor-patient relationships, offering effective management strategies. Utilizing an empirical legal research approach, data will be gathered through observation and in-depth interviews. This study reveals how social, economic, and educational factors impact contract breaches at Mitra Masyarakat Timika Papua Hospital. Social conditions, culture, and environment shape patient-therapeutic interactions. Economic constraints and lack of insurance impede treatment payment, while limited education affects medical understanding and rights comprehension. Strategies like financial flexibility, assistance, and improved cost information manage risks. Breaches cause psychological impact and strained doctor-patient ties. Effective strategies encompass communication, support, re-evaluation, dispute resolution, education, and improved doctor communication. Holistic, empathetic approaches maintain care quality and trust